Implementasi Marketing Mix di Rumah Sakit PKU Muhammadiyah Sukoharjo - M. Indrawan Nur Huda; Agus Trijono; Anton Susanto (Journal of Educational Innovation and Public Health, 2024)
The large number of hospitals in Sukoharjo City makes the people of Sukoharjo City have many choices to determine where they will use health services. The community is very selective about services in hospitals, so that aspects in the Marketing Mix become a benchmark for determining whether or not patients will use health services at the hospital. Marketing Mix is ​​a series of marketing tools used by companies or hospitals continuously to achieve their marketing goals in the target market. This study aims to explore and find obstacles in the implementation of the marketing mix at PKU Muhammadiyah Hospital, Sukoharjo. The study used a qualitative descriptive method with a cross-sectional approach and data collection techniques using in-depth interviews with key informants and specialist informants at the hospital. The results of the study showed that marketing mix components such as products, people, and promotions have been implemented well, although there are still some challenges. Excellent services such as ERACS and stitch-free eye surgery have succeeded in attracting patient interest, but promotion through social media has not been optimal, based on a comparison between the number of patients each month and interactions on social media, it was concluded that social media promotion is still not optimal because the number of interactions is still ≥50% of the number of patients. In addition, hospitals face obstacles in implementing telemedicine and homecare services. Recommendations provided include improving digital promotion strategies and developing innovative services to improve hospital competitiveness and hospitals must also consider the suitability between educational background and the work assigned.